2003
DOI: 10.1046/j.1440-1673.2003.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Views of Australian and New Zealand radiation oncologists and registrars about evidence‐based medicine and their access to Internet based sources of evidence

Abstract: In order to determine the views of Australian and New Zealand (ANZ) radiation oncologists and registrars about evidence-based medicine (EBM) and their access to, and use of, Internet-based EBM resources such as MEDLINE and the Cochrane Library, a self-administered postal survey was sent out in December 2000. A total of 191 of 243 practicing ANZ radiation radiation oncologists (138) and registrars (53) responded (78.6% response rate). The main outcome measures were: (i) views about EBM and its promotion; (ii) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 16 publications
(31 reference statements)
9
39
1
2
Order By: Relevance
“…On comparing the difference in history of previous training between users and nonusers, a strong association was found between EBM training and EBM use, and our findings were similar to those of other studies [24,[27][28][29][30] that showed that, although training in EBM was received only by a small proportion of clinicians, this helped them to be more frequent users (twice as others). Similarly, research methodology courses were twice as common among users than among nonusers.…”
Section: Discussionsupporting
confidence: 89%
“…On comparing the difference in history of previous training between users and nonusers, a strong association was found between EBM training and EBM use, and our findings were similar to those of other studies [24,[27][28][29][30] that showed that, although training in EBM was received only by a small proportion of clinicians, this helped them to be more frequent users (twice as others). Similarly, research methodology courses were twice as common among users than among nonusers.…”
Section: Discussionsupporting
confidence: 89%
“…Since its publication in 1998, it has been used widely, with various modifications, to study the attitudes, knowledge, and barriers to practice of EBM in different settings. 2,10,11 The McColl questionnaire also assesses the understanding of the responder, of common technical terms used in EBM and their access to databases relevant to the practice of EBM.…”
Section: Methodsmentioning
confidence: 99%
“…Web sites of professional, government, education and commercial organisations are utilised by health professionals to access online journals, health and medical databases, practice guidelines, image banks and case studies as well as information on professional development activities (see for example 31,[32][33][34][35][36][37][38][39]. Internet based communication tools of e-mail, listservs and discussion forums are used by health professionals to consult with colleagues nationally and internationally (31,32,34,35,39).…”
Section: Learning Mediated By Information Sourcesmentioning
confidence: 99%